Targeted nanoparticles – a promising opportunity in cancer therapy – Review - Černá, Tereza; Eckschlager, Tomáš; Stiborová, Marie (Journal of Metallomics and Nanotechnologies, 2016)
Nanoparticles as drug delivery vehicles pose an exciting and promising future for cancer treatment, and offer particular benefits not only for cancer treatment, but also for overcoming of multidrug resistance in cancer tissues. Targeted delivery of anti-neoplastic drugs by nanoparticles promises enhanced drug efficacy, selectivity and reduced systemic toxicity. Nanoparticle systems have unique properties that allow for both passive and active targeting of tumors. Active targeting of nanoparticles, that usually involve surface proteins known to be upregulated in cancer cells, increases accumulation in a tumor. Targeting molecules include antibodies or their fragments, aptamers, or small molecules. This review describes a comprehensive overview of different targeting of nanodrugs.
Keywords: Neoplasms; Nanoparticles; nádory; nosiče léků; Drug Carriers; lidé; Antineoplastic Agents; protinádorové látky; nanočástice; Humans